Endovascular repair of posterior communicating artery aneurysms, associated with oculomotor nerve palsy: A review of nerve recovery. Issue 3 (June 2015) - Sheehan, Mark John; Dunne, Ruth; Thornton, John; Brennan, Paul; Looby, Seamus; O'Hare, Alan
Purpose: Oculomotor nerve palsy (ONP) is often the presenting symptom in patients with posterior communicating artery (PCOMM) aneurysms with variable recovery of oculomotor nerve function following treatment. In this study we report the ophthalmologic outcome of 20 patients treated by endovascular coiling for PCOMM aneurysm-induced ONP. Methods: We performed 230 PCOMM aneurysm endovascular coilings between the years 2006 and 2011, of which 20 cases presented with ONP. We recorded the degree of nerve recovery – complete, partial or none – while also documenting other predictive factors, such as degree of pre-intervention nerve deficit, presence of subarachnoid haemorrhage (SAH), size and location of the PCOMM aneurysm and length of follow-up. Results: Of the 20 patients, 9 (45%) presented with complete ONP and 11 (55%) with partial ONP. After an average follow-up period of 16 months, all patients achieved oculomotor nerve recovery; 9 (45%) patients had complete recovery and 11 (55%) patients had partial recovery. Of the 9 patients who presented with complete ONP, 5 (56%) patients made a complete recovery and 4 (44%) made a partial recovery. Of the 11 patients who initially presented with partial ONP, 4 (36%) made a complete recovery and 7 (64%) made a partial recovery. 7 (35%) patients also had a SAH, of whom 3 (43%) made a complete recovery with 4 (57%) making a partial recovery. Conclusions: ONP can occur with PCOMM aneurysm with or without SAH. Endovascular coiling is an effective treatment for ONP due to PCOMM aneurysms.